2006
DOI: 10.1261/rna.108106
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of endogenes mediated by a transitive silencing signal

Abstract: Some RNA silencing systems in plants, nematodes, and fungi show spreading of silencing along target sequences, termed transitive silencing. Here, we address the question of whether endogenous targets can be silenced by a transitive silencing signal in plants. In transgenic Arabidopsis thaliana plants that harbored a silencing-inducing locus and a transgenic chimeric primary target, silencing of a secondary transgenic target occurred and the expression of the endogenous catalase genes was downregulated, coincid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Here, we study in more detail the 3# to 5# spreading previously observed with the XYZ-silencing system (Van Houdt et al, 2003;Bleys et al, 2006a) by using primary targets Y 98 , Y 250 , and Y 500 in which 98 nt, 250 nt, and 500 nt of the CAT2 sequence, respectively, were inserted between the nptII-3#chs end targeted by the silencing inducer X 21 and the upstream region homologous to a transgenic gus target Z c . We demonstrate that the length of the CAT2 inserts influences the timing and efficiency of silencing induced by secondary CAT2-and gus-specific siRNAs originating from the primary target transcripts.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Here, we study in more detail the 3# to 5# spreading previously observed with the XYZ-silencing system (Van Houdt et al, 2003;Bleys et al, 2006a) by using primary targets Y 98 , Y 250 , and Y 500 in which 98 nt, 250 nt, and 500 nt of the CAT2 sequence, respectively, were inserted between the nptII-3#chs end targeted by the silencing inducer X 21 and the upstream region homologous to a transgenic gus target Z c . We demonstrate that the length of the CAT2 inserts influences the timing and efficiency of silencing induced by secondary CAT2-and gus-specific siRNAs originating from the primary target transcripts.…”
Section: Discussionmentioning
confidence: 98%
“…The production of plants harboring the silencing-inducing locus X 21 and locus Z c has been described previously (Bleys et al, 2006a). Locus X 21 is an IR transgene locus with two convergently transcribed neomycin phosphotransferase II (nptII) reporter genes (P35S-nptII-3#chs) that show posttranscriptional gene silencing.…”
Section: Plant Materials and Crossesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, Drosophila and mammals neither have RdRPs encoded in their genomes nor have the capability to induce RNAi silencing in cells that do not themselves produce siRNAs. 10 Moreover, it appears that the RNAi machinery is not involved in the heterochromatic silencing of multiple copies of transgenes in mammalian cells. 11 While some of this diversity can be attributed to different components of the pathway in different species, some of the diversity may be due to different mechanisms of pathway regulation.…”
Section: Introductionmentioning
confidence: 99%